2020
DOI: 10.1101/2020.07.26.221937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quorum Sensing Regulates ‘swim-or-stick’ Lifestyle in the Phycosphere

Abstract: Originality-significance statementMotility and biofilm formation are processes regulated by quorum sensing (QS) in bacteria. Both functions are believed to play an important role in interactions between bacteria and phytoplankton. Here, we show that two bacterial symbionts from the microbial community associated with a ubiquitous diatom switch their motile lifestyle to attached cells while an opportunist bacterium from the same community is incapable of attachment, despite possessing the genetic machinery to d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 122 publications
(143 reference statements)
0
8
0
Order By: Relevance
“…5C ). QS signaling molecule has been shown to alter the bacterial composition ( 28 ), and QS-QQ are known to regulate bacterial chemotaxis, biofilm formation, and adhesion to phytoplankton environment ( 29 ). With this potential for such a profound effect, the contribution of these genes to the shift in bacterial community composition and the reestablishment of mutualism within the coculture system cannot be denied.…”
Section: Discussionmentioning
confidence: 99%
“…5C ). QS signaling molecule has been shown to alter the bacterial composition ( 28 ), and QS-QQ are known to regulate bacterial chemotaxis, biofilm formation, and adhesion to phytoplankton environment ( 29 ). With this potential for such a profound effect, the contribution of these genes to the shift in bacterial community composition and the reestablishment of mutualism within the coculture system cannot be denied.…”
Section: Discussionmentioning
confidence: 99%
“…2015). Recent findings also show that bacterial symbionts use quorum sensing to promote biofilm formation and phycosphere colonization, while diatoms can directly modulate bacterial colonization and suppress the opportunist attachment via secondary metabolites such as azelaic acid and rosmarinic acid (a quorum sensing mimic) (Fei et al . 2020; Shibl et al .…”
Section: Discussionmentioning
confidence: 99%
“…2015; van Tol, Amin and Armbrust 2017), and sexual reproduction (Cirri, Vyverman and Pohnert 2018; Cirri et al . 2019), while diatoms can directly modulate the bacterial community via secondary metabolite production (Fei et al . 2020; Shibl et al .…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial movement and biofilm development are controlled by QS. For instance, Fei et al [ 83 ] have shown that the QS influences the colonization of diatom surfaces by the bacteria. The study evaluated the association of three bacterial symbionts – Phaeobacter sp.…”
Section: Microalgae-bacterial Systems For Wastewater Treatmentmentioning
confidence: 99%